2021
DOI: 10.17509/ijotis.v1i1.39403
|View full text |Cite
|
Sign up to set email alerts
|

The attitude of Distance Learners towards the Utilization of Learning Management System (A case study of National Open University of Nigeria)

Abstract: One significant innovative technology to expand teaching and learning mostly in Distance Education is Learning Management System (LMS). LMS allow learning institutions to offer a larger number of courses online whether full or blended, by providing institutions with a digital space for numerous purpose which includes documentation, tracking and online training. However, for the relevance of LMS within an education context, distance learners’ attitudes towards the use of LMS must be investigated. The study ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…Over the years, its development due to the emergence of the internet cannot be unseen. The promised optimal use eventually entered the world of education and is now considered a mainstay of online education infrastructure [10].…”
Section: Learning Management Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, its development due to the emergence of the internet cannot be unseen. The promised optimal use eventually entered the world of education and is now considered a mainstay of online education infrastructure [10].…”
Section: Learning Management Systemmentioning
confidence: 99%
“…the utilization of learning management systems (LMS) can be administered in various ways. Ajijola, Ogunlade, and Aladesusi [10] studied the students' attitudes toward LMS, while Mahali, Changilwa, and Anyona [11] examined the influence of the level of training on the utilization of LMS. Both studies found positive results regarding their focus of investigation (i.e., attitudes and level of training), supporting that these results affected how participants view LMS' relevance to the educational context.…”
Section: Investigatingmentioning
confidence: 99%